2016
DOI: 10.1242/dev.141069
|View full text |Cite
|
Sign up to set email alerts
|

DNA damage-induced Lok/CHK2 activation compromises germline stem cell self-renewal and lineage differentiation

Abstract: Stem cells in adult tissues are constantly exposed to genotoxic stress and also accumulate DNA damage with age. However, it remains largely unknown how DNA damage affects both stem cell selfrenewal and differentiation. In this study, we show that DNA damage retards germline stem cell (GSC) self-renewal and progeny differentiation in a Lok kinase-dependent manner in the Drosophila ovary. Both heatshock-inducible endonuclease I-CreI expression and X-ray irradiation can efficiently introduce double-strand breaks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
52
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(58 citation statements)
references
References 74 publications
(110 reference statements)
4
52
1
Order By: Relevance
“…Because it is thought that DNA damage associated with HD causes the germline-loss phenotype 17,40 , one possible mechanism underlying MDRG is that Myc mediates DDR, which induces cell-cycle arrest and apoptosis in the germline 41,42 . In Drosophila oogenesis, when female GSCs and their daughter cells are exposed to DNA damage, loki/Chk2 is required for cell-cycle arrest of GSCs and the loss of these cells 20,22 . Moreover, in meiotic cells, p53 acts downstream of loki/Chk2 to induce apoptosis in response to DNA damage 18,21 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Because it is thought that DNA damage associated with HD causes the germline-loss phenotype 17,40 , one possible mechanism underlying MDRG is that Myc mediates DDR, which induces cell-cycle arrest and apoptosis in the germline 41,42 . In Drosophila oogenesis, when female GSCs and their daughter cells are exposed to DNA damage, loki/Chk2 is required for cell-cycle arrest of GSCs and the loss of these cells 20,22 . Moreover, in meiotic cells, p53 acts downstream of loki/Chk2 to induce apoptosis in response to DNA damage 18,21 .…”
Section: Discussionmentioning
confidence: 99%
“…This germline-loss phenotype is thought to be caused by DNA damage associated with P-element mobilization 17 . In ovarian germline cells, DNA damage induces cell-cycle arrest and apoptosis via the functions of two DNA damage response (DDR) genes, loki (also known as mnk) encoding checkpoint kinase 2 (Chk2) and p53 [18][19][20][21] . In early oogenesis, loki/Chk2 is required for cell-cycle arrest of the germline stem cells (GSCs) and their daughters in response to DNA damage 18,20 .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In Drosophila, Chk2-signaling triggered by DNA damage, replication stress or nuclear lamina dysfunction induces GSC loss (Barton et al, 2018;Ma et al, 2016;Molla-Herman et al, 2015). Our previous study showed that removal of Chk2 in vas mutant flies fully restores oogenesis, while progeny embryos succumb to transposon up-regulation and DNA damage (Durdevic et al, 2018).…”
Section: Discussionmentioning
confidence: 99%